Hadith #2806 - Sahih al-Bukhari - Khalid bin Ma'dan خالد بن معدان (Sahih al-Bukhari)
That ‘Umair bin Al-Aswad Al-Anasi told him that he went to ‘Ubada bin As-Samit while he was staying in his house at the sea-shore of Hims with (his wife) Um Haram. ‘Umair said. Um Haram informed us that she heard the Prophet (ﷺ) saying, “Paradise is granted to the first batch of my followers who will undertake a naval expedition.” Um Haram added, I said, ‘O Allah’s Messenger (ﷺ)! Will I be amongst them?’ He replied, ‘You are amongst them.’ The Prophet (ﷺ) then said, ‘
Grade: Sahih